Dynamics of Social Mobility during the COVID-19 Pandemic in Canada - Mutlu Yuksel; Yigit Aydede; Francisko Begolli (Institute of Labor Economics (IZA), 2020)
As the number of cases increases globally, governments and authorities have continued to use mobility restrictions that were, and still are, the only effective tool to control for the viral transmission. Yet, the relationship between public orders and behavioral parameters of social distancing observed in the community is a complex process and an important policy question. The evidence shows that adherence to public orders about the social distancing is not stable and fluctuates with degree of spatial differences in information and the level of risk aversion. This study aims to uncover the behavioural parameters of change in mobility dynamics in major Canadian cities and questions the role of people's beliefs about how contagious the disease is on the level of compliancy to public orders. Our findings reveal that the degree of social distancing under strict restrictions is bound by choice, which is affected by the departure of people's beliefs from the public order about how severe the effects of disease are. Understanding the dynamics of social distancing thus helps reduce the growth rate of the number of infections, compared to that predicted by epidemiological models.
Keywords: I20; I26; J24; 330; COVID-19; mobility; transmission; viral infections